2016
DOI: 10.5897/jmpr2016.6044
|View full text |Cite
|
Sign up to set email alerts
|

Potency of extracts of selected plant species from Mbeere, Embu County-Kenya against Mycobacterium tuberculosis

Abstract: Tuberculosis is a serious chronic infectious disease affecting large global population. While efforts to control tuberculosis have intensified, they are challenged by rapid drug resistance development. For this reason, prospecting for compounds with potential antituberculous activity have been stepped up. The current study was done in a participatory appraisal manner to identify ten plants commonly used for management of "persistent coughs". Bioassays were conducted against Mycobacterium tuberculosis (H37Rv AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…ex Miq. Urticaceae Munyango (Luganda) Herb Leaves Uganda [ 7 ] Garcinia buchananii Baker Clusiaceae Musaali (Luganda) Tree Stem bark, Root bark Uganda, Kenya, Tanzania [ 7 , 10 , 12 ] Gnaphalium purpureum L. Asteraceae Omuya (Luganda) Herb Leaves Uganda [ 7 ] Gnidia buchananii Gilg Thymelaeaceae Not reported Herb Roots Kenya [ 49 ] Gomphocarpus physocarpus E. Mey. Apocynaceae Gashaho Herb Leaves Uganda [ 10 ] Gutenbergia cordifolia Benth.…”
Section: Resultsmentioning
confidence: 99%
“…ex Miq. Urticaceae Munyango (Luganda) Herb Leaves Uganda [ 7 ] Garcinia buchananii Baker Clusiaceae Musaali (Luganda) Tree Stem bark, Root bark Uganda, Kenya, Tanzania [ 7 , 10 , 12 ] Gnaphalium purpureum L. Asteraceae Omuya (Luganda) Herb Leaves Uganda [ 7 ] Gnidia buchananii Gilg Thymelaeaceae Not reported Herb Roots Kenya [ 49 ] Gomphocarpus physocarpus E. Mey. Apocynaceae Gashaho Herb Leaves Uganda [ 10 ] Gutenbergia cordifolia Benth.…”
Section: Resultsmentioning
confidence: 99%
“…Same authors also identified tannins, saponins and sterols in the stem bark extracts of the species. Dichrostachys cinerea extracts demonstrated antituberculous activities which could be attributed to the presence of bioactive compounds such as alkaloids, diterpenes, flavonoid, phytosterols, tannis and triterpenes [34]. Similarly, Peltophorum africanum bark and root extracts exhibited antibacterial activities against the respiratory infections strains Staphylococcus aureus, Streptococcus pyogenes and Klebsiella pneumoniae [35].…”
Section: Fidelity Level (Fl) and Use Value (Uv)mentioning
confidence: 99%
“…In East Tropical Africa, E. ingens is used for the treatment of snakebites (Ernst et al, 2015). In addition to its traditional medicinal uses, there are reports on its ichthyocidal, antituberculous, antimicrobial and antifungal activities (Kena, 2016;Njeru and Meshack, 2016;Ross and Steyn, 2004).…”
Section: Introductionmentioning
confidence: 99%